Intelligent response type organic light-emitting material as well as preparation method and application thereof
By using phenothiothio or dibenzodioxin as donor and 3,4,5,6-tetrafluorophthalitrile as acceptor, intelligent responsive organic donor acceptor composite material was prepared by self-assembly through grinding method, which solved the problems of high preparation cost and poor stability of existing materials, and achieved efficient optical performance and reversibility.
Patent Information
- Application Number
- CN202411851453.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing intelligent responsive organic luminescent material preparation methods lead to high production costs, poor material stability, and need to improve the luminescent intensity and luminescent life.
The intelligent responsive organic donor receptor composite material was prepared by self-assembly by grinding.
The material has excellent optical properties and aggregation-induced luminescence properties, is very sensitive to temperature changes, the response speed accelerates with the increase of temperature, and has good reversibility, allowing multiple writing and erasing.
Smart Images

Figure CN119685006A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic light-emitting materials, and in particular to an intelligent response type organic light-emitting material and a preparation method and application thereof. Background Art
[0002] With the rapid development of science and technology, people's requirements for material performance are increasing day by day, especially in the fields of information technology, biomedicine, environmental monitoring, etc., traditional materials can no longer meet the complex and changing application requirements. Smart responsive materials, as a new type of material that can quickly respond to external stimuli (such as temperature, light, electric field, pH value, etc.) and change its own performance, have received widespread attention and research in recent years. Among them, smart responsive organic light-emitting materials, as an important branch, not only have excellent luminescent properties, but also can realize real-time monitoring and regulation of the external environment through intelligent response mechanisms. Therefore, they show great application potential in display technology, sensors, bioimaging, ultrafast lasers and other fields.
[0003] In recent years, researchers have continuously carried out technological innovation and made significant progress in designing a series of new donor-acceptor materials with specific molecular structures and organic light-emitting materials with stable properties. Organic donor-acceptor complexes are organic materials that are self-assembled by electron donors and electron acceptors through non-covalent intermolecular interactions. They can not only maintain the properties of the original components, but also show novel properties through eutectic engineering. In addition, their intermolecular interactions are weak and they are more sensitive to the external environment. The internal structure or force of crystalline materials is easily changed under external stimulation, thus showing unique physical properties.
[0004] Although important progress has been made in the research of smart responsive organic light-emitting materials, the research on two-component smart light-emitting materials is still in its initial stage. The existing preparation methods of smart responsive organic light-emitting materials lead to high production costs, poor stability of the prepared materials, and the luminescence intensity and luminescence life need to be further improved. Summary of the invention
[0005] The present invention provides an intelligent responsive organic light-emitting material and a preparation method and application thereof, which effectively solve the technical problems of high production cost, poor stability of the prepared organic light-emitting material, insufficient luminous intensity and short luminous lifetime caused by the existing preparation method of the intelligent responsive organic light-emitting material. The present invention uses thiophene (OSA) or dibenzodioxin (OOA) as a donor and 3,4,5,6-tetrafluorophthalonitrile (TFBN) as an acceptor to successfully synthesize OSA-TFBN or OOA-TFBN intelligent organic donor-acceptor complex materials, i.e., intelligent responsive organic light-emitting materials. The material has excellent optical properties and aggregation-induced luminescence properties, is very sensitive to temperature changes, and the response speed increases with increasing temperature. The material also has good reversibility and can be written and erased multiple times.
[0006] The first object of the present invention is to provide a method for preparing an intelligent response type organic light-emitting material, comprising the following steps:
[0007] 3,4,5,6-tetrafluorophthalonitrile (structural formula: The molecular weight is 200.093, the melting point is 81-86℃) as the receptor, with phenoxathiol (structural formula: Molecular weight is 200.256, melting point is 52-56°C) or dibenzo-p-dioxin (structural formula: The molecular weight is 184.191 and the melting point is 200° C.) as a donor, and the acceptor and the donor are self-assembled by a grinding method to obtain an intelligent responsive organic light-emitting material.
[0008] As a preferred embodiment, the molar ratio of the 3,4,5,6-tetrafluorophthalonitrile to the dibenzoheterocyclohexadiene compound is 1:1.
[0009] As a preferred embodiment, 3,4,5,6-tetrafluorophthalonitrile and phenoxathiol or dibenzodioxin are mixed and ground to obtain a smart response type organic light-emitting material.
[0010] As a preferred embodiment, the grinding time is 1 to 4 minutes.
[0011] The second object of the present invention is to provide an intelligent responsive organic light-emitting material prepared by the above preparation method.
[0012] As a preferred implementation, the aggregation-induced luminescence of the smart responsive organic light-emitting material is yellow light or blue-green light.
[0013] The third object of the present invention is to provide an application of the above-mentioned intelligent responsive organic light-emitting material in the preparation of temperature responsive anti-counterfeiting materials.
[0014] As a preferred implementation, the application specifically includes: preparing a dichloromethane solution of the smart responsive organic light-emitting material, and using the solution to soak the anti-counterfeiting material, and drying it at room temperature.
[0015] As a preferred implementation manner, the concentration of the dichloromethane solution of the smart response type organic light-emitting material is 0.05 mol / L to 0.07 mol / L.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] The present invention provides an intelligent response type organic light-emitting material and a preparation method and application thereof. 3,4,5,6-tetrafluorophthalonitrile is used as an acceptor, thiophene or dibenzodioxin is used as a donor, and the acceptor and the donor are self-assembled by a grinding method to obtain an intelligent response type organic light-emitting material. When the donor material is thiophene, the composite emits yellow light. When the donor material is dibenzodioxin, the composite emits blue light. Through in-depth research on the composite, it is found that the composite has aggregation-induced luminescence properties, and the composite material is very sensitive to temperature changes. The response time accelerates with increasing temperature. The higher the temperature, the faster the response speed, and the lower the temperature, the slower the response speed. When the temperature rises to a certain critical point, the luminescence of the composite will be quenched, and the heat source will be removed. As the temperature decreases, the composite gradually returns to its original luminescent color, that is, it exhibits a reversible temperature fluorescence response. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 These are the fluorescence images of phenoxathiol (OSA), dibenzodioxin (OOA), thianthrene (SSA) and 3,4,5,6-tetrafluorophthalonitrile (TFBN) under ultraviolet light at room temperature in the present invention, wherein Figure A is OSA, Figure B is OOA, Figure C is SSA, and Figure D is TFBN.
[0019] Figure 2 This is a fluorescence image change diagram of OSA and TFBN ground for 1 to 4 minutes at room temperature according to the present invention.
[0020] Figure 3 This is a fluorescence image change diagram of OOA and TFBN grinding for 1 to 4 minutes at room temperature according to the present invention.
[0021] Figure 4 This is a fluorescence image change diagram of SSA and TFBN ground for 1 to 4 minutes at room temperature according to the present invention.
[0022] Figure 5 Figure a in the middle is the fluorescence spectra of OSA, TFBN, and OSA-TFBN; Figure b is the fluorescence spectra of OOA, TFBN, and OOA-TFBN; Figure c is a comparison of the XRD diffraction images of SSA, TFBN, and SSA-TFBN.
[0023] Figure 6 Figure a in the middle is a comparison of the XRD diffraction images of OSA, TFBN, and OSA-TFBN; Figure b is a comparison of the XRD diffraction images of OOA, TFBN, and OOA-TFBN.
[0024] Figure 7 Figure a in the middle shows the emission spectra of OSA-TFBN in mixed solvents of DMSO and H2O in different proportions; Figure b shows the emission spectra of OSA, TFBN, and OSA-TFBN in DMSO solution.
[0025] Figure 8 Figure a in the middle shows the emission spectra of OOA-TFBN in mixed solvents of DMSO and H2O in different proportions; Figure b shows the emission spectra of OOA, TFBN, and OOA-TFBN in DMSO solution.
[0026] Fig. 9 This is a graph of the reaction of OSA and TFBN at room temperature for 72 hours according to the present invention.
[0027] Fig.10 This is a graph showing the response speeds of OSA and TFBN at different temperatures in the present invention.
[0028] Fig.11 This is a fluorescence quenching image change diagram of OSA-TFBN at 45°C of the present invention.
[0029] Fig.12 This is a fluorescence recovery image change diagram of OSA-TFBN at room temperature according to the present invention.
[0030] Fig.13 This is a graph of the reaction of OOA and TFBN at room temperature for 72 hours according to the present invention.
[0031] Fig.14 It is the response speed diagram of OOA and TFBN at different temperatures of the present invention.
[0032] Fig.15 This is a fluorescence quenching image change diagram of OOA-TFBN at 75°C of the present invention.
[0033] Fig.16 This is a fluorescence recovery image change diagram of OOA-TFBN at room temperature of the present invention.
[0034] Fig.17 Graphs showing the response speeds of SSA and TFBN at different temperatures of the present invention; wherein Graph A is at 70°C, Graph B is at 80°C, Graph C is at 90°C, and Graph D is at 100°C.
[0035] Fig.18 Schematic diagram of the reversible luminescence process of OSA-TFBN under ultraviolet light irradiation of the present invention.
[0036] Fig.19 Schematic diagram (three-dimensional diagram) of four rounds of reversible fluorescence changes of OSA-TFBN of the present invention.
[0037] Fig. 20 Schematic diagram (two-dimensional diagram) of four rounds of reversible fluorescence changes of OSA-TFBN of the present invention. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.
[0039] In view of the fact that the research on two-component smart luminescent materials is still in its initial stage, the existing preparation methods of smart responsive organic luminescent materials result in high production costs, poor stability of the prepared materials, and the luminescent intensity and luminescent life need to be further improved, the present invention provides a smart responsive organic luminescent material and its preparation method and application.
[0040] The technical scheme and technical effects of the present invention are described below in conjunction with embodiments.
[0041] Experimental steps:
[0042] Preparation: Take the required medicines out of the medicine cabinet, prepare two clean medicine spoons, a clean natural agate mortar and some paper towels. Calculate the required grams of the guest material based on the relative molecular mass of the host material with a molar ratio of 1:1.
[0043] Turn on the electronic balance and press the Tare / Zero key. The weighing table of the required materials is shown in Table 1. After the balance reading stabilizes, record the number of grams weighed.
[0044] Transfer the medicine on the weighing paper to the two sides of the mortar, illuminate it with ultraviolet light, observe the luminescent color of the single-component medicine and take photos to record. Figure 1 As shown, before grinding, TFBN is a white crystal that emits blue light under ultraviolet light, OSA is a white crystal that hardly emits light under ultraviolet light, and OOA is a white powder that hardly emits light under ultraviolet light.
[0045] Table 1 Weighing table of required materials
[0046] Luminescent Materials Relative molecular weight Amount to be taken / g Actual amount / g TFB 200.093 0.0400g 0.0408g OSA 200.256 0.0400g 0.0402g OOA 184.191 0.0368g 0.0372g
[0047] Example 1
[0048] A method for preparing an intelligent responsive organic light-emitting material comprises the following steps:
[0049] 0.0402 g OSA and 0.0408 g TFBN were poured into a mortar and ground clockwise for 4 min to obtain an organic charge transfer complex, which was recorded as OSA-TFBN complex. During grinding, ultraviolet light was used for observation. The color changes under fluorescent light and ultraviolet light were observed every 1 min of grinding, and photographed and recorded. The fluorescence image is shown in Figure 2 As shown, it was found that OSA and TFBN reacted with slight force during the grinding process. As the grinding time increased, the powder color turned slightly yellow under fluorescent light, and the composite material showed a bright yellow fluorescence under ultraviolet light, which was significantly different from the single-component material.
[0050] Example 2
[0051] A method for preparing an intelligent responsive organic light-emitting material comprises the following steps:
[0052] 0.0372 g OOA and 0.0408 g TFBN were poured into a mortar and ground clockwise for 4 min to obtain an organic charge transfer complex, which was recorded as OSA-TFBN complex. During grinding, ultraviolet light was used for observation. The color changes under fluorescent light and ultraviolet light were observed every 1 min of grinding, and photographed and recorded. The fluorescence image is shown in Figure 3 As shown, with the increase of grinding time, the powder color becomes white under fluorescent light, and the composite material exhibits a blue fluorescence under ultraviolet light that is significantly different from the single-component material.
[0053] In order to further demonstrate the technical effect of the present invention, the present invention also sets a comparative example, which is as follows:
[0054] Comparative Example 1
[0055] A method for preparing a SSA-TFBN dopant comprises the following steps:
[0056] 0.0432 g of thianthrene (SSA structural formula: The molecular weight of the mixture was 216.32) and 0.0400 g TFBN were poured into a mortar and ground clockwise for 4 min to obtain a dopant of SSA and TFBN, which was recorded as SSA-TFBN. During the grinding process, ultraviolet light was used for observation. The color changes under fluorescent light and ultraviolet light were observed every 1 min of grinding, and photographed and recorded. The fluorescence image is shown in the figure: Figure 4 As shown, no matter how long the powder is ground, the powder is white under fluorescent light, and the SSA-TFBN dopant material does not show a fluorescent color different from the single-component material under ultraviolet light.
[0057] The structure and performance of the smart responsive organic light-emitting material prepared above were characterized. The specific process and results are as follows:
[0058] 1. Structural Characterization
[0059] 1.1 Fluorescence spectrum
[0060] ① Preparation: UV lamp, tweezers, weighing paper, toilet paper, anhydrous ethanol, dichloromethane, filter, choose solid sample tank or liquid sample tank according to the state of the substance to be tested.
[0061] ② Turn on the computer, instrument, and software in sequence, turn on the xenon lamp, and preheat for half an hour to reduce experimental errors.
[0062] ③ Select a suitable excitation light source and set the emission light source to the wavelength range of the sample to be tested. Re-measure the emission light source based on the excitation light source to measure the optimal emission spectrum under appropriate conditions.
[0063] ④After the test, turn off the instrument and computer and clean the desk.
[0064] ⑤ Draw a fluorescence spectrum, and analyze the maximum emission peak, intensity, etc. of the material based on the drawn fluorescence spectrum.
[0065] The organic donor-acceptor complex is obtained by self-assembly of the donor and the acceptor. The donor OSA emits almost no light under ultraviolet light, while the acceptor TFBN emits blue light under ultraviolet light. After grinding the two materials together, the OSA-TFBN complex material emits yellow light. The donor OOA emits almost no light under ultraviolet light, while the acceptor TFBN emits blue light under ultraviolet light. The ground OOA-TFBN complex emits bright blue light that is different from the single-component material. The luminescent color of the products has changed significantly, indicating that a new substance has been generated. In order to prove the generation of a new organic donor-acceptor complex material, the spectral images of the complex and the donor and acceptor materials were tested and compared using a fluorescence spectrometer to further prove the generation of a new substance, rather than simple physical doping.
[0066] Depend on Figure 5 As shown in Figure a, the maximum emission peak of the donor material OSA is 445nm, and it hardly emits light under ultraviolet light. The maximum emission peak of the acceptor material TFBN is 325nm, and it emits blue light under ultraviolet light. However, the maximum emission peak of the OSA-TFBN composite material is 535nm, and it emits yellow light. Compared with the fluorescence spectra of the two single-component materials, the fluorescence wavelength of the composite is red-shifted, which indicates that the fluorescence of the composite comes from the joint action of two molecules, rather than the luminescence of a single substance.
[0067] Figure 5As shown in Figure b, the maximum emission peak of the donor material OOA is 375nm, and it hardly emits light under ultraviolet light. The maximum emission peak of the acceptor material TFBN is 325nm, and it emits blue light under ultraviolet light. However, the maximum emission peak of the OOA-TFBN composite material is 485nm, which is obviously different from the blue light emission of the single-component material. Compared with the fluorescence spectra of the two single-component materials, the fluorescence wavelength of the composite is obviously red-shifted, which also shows that the fluorescence of the composite comes from the joint action of two molecules, rather than the luminescence of a single substance.
[0068] Depend on Figure 5 As can be seen from Figure C, since the single-component material SSA hardly emits light, the SSA-TFBN two-component material exhibits a single emission spectrum of TFBN during spectral testing.
[0069] 1.2XRD spectrum
[0070] ① Preparation: UV lamp, alcohol cotton balls, tweezers, weighing paper, toilet paper, and sample preparation trough.
[0071] ② Turn on the circulating condensing water, power switch, and panel switch in sequence according to the operating procedures, and adjust the scanning angle to 5° to 60° according to the experimental needs. Complete the XRD test according to the operating procedures and obtain the XRD spectrum. Use Origin to draw the spectrum and analyze it.
[0072] In order to further prove the formation of organic donor-acceptor complex, we used X-ray powder diffractometer to further characterize the complex and single-component donor and acceptor materials. Figure 6 As shown in Figure a, the diffraction pattern of OSA-TFBN is significantly different from that of single-component OSA and TFBN. A new diffraction peak appears at 10° to 30°, indicating that during the grinding process, OSA-TFBN is not simply physically doped, but forms a relatively stable structure under the stimulation of external forces, thus producing a diffraction peak different from that of a single component. Figure 6 As can be seen from Figure b, the diffraction pattern of the grinding product OOA-TFBN is significantly different from the diffraction patterns of single-component OOA and TFBN. New diffraction peaks appear at 10°~30°, indicating that during the grinding process, OOA-TFBN is not simply physically doped, but forms a relatively stable structure under the stimulation of external forces, thus producing diffraction peaks different from those of single components.
[0073] 2. Aggregation-induced emission properties
[0074] 2.1 Aggregation-induced emission (AIE) sample preparation
[0075] Aggregation-induced emission (AIE) is a fluorescence phenomenon that is different from traditional solution-state fluorescence behavior. Traditional fluorescent materials will be quenched in solution due to intermolecular aggregation, while AIE substances do not emit light in solution, but when they form aggregates or solid structures, they will show obvious luminescence characteristics.
[0076] The experimental steps are as follows:
[0077] ① According to the molar concentration formula: C = n / V, calculate the concentration of 10mL of the complex material stock solution to be 7×10-2mol / L. Prepare a 10mL glass bottle, a 1000μL pipette and an adapter tip, dimethyl sulfoxide solution (DMSO), deionized water, and twenty 3mL small glass bottles.
[0078] ② After calculation, it was found that the two-component material required for the AIE of OSA-TFBN composite material was 0.2800g, and the two-component material required for the AIE of OOA-TFBN composite material was 0.02702g. The required two-component materials were weighed with an electronic balance and placed in a 10mL glass bottle. 10mL of DMSO solution was added to each glass bottle, shaken evenly, and the original solution labels were attached and set aside for later use.
[0079] ③ Use a marker pen to mark the caps of ten 3mL glass bottles with 0, 10, 20, 30, 40, 50, 60, 70, 80, and 90 to represent the water content of the solution. Add 300μL of the stock solution to each glass bottle, add the corresponding amount of deionized water according to the mark on the cap, and make up the less than 3mL with DMSO solution. The actual amount of various solutions is shown in Table 2.
[0080] Table 2 Liquid volume required for aqueous solutions of different concentrations
[0081]
[0082]
[0083] ④ Place the prepared solutions with different water contents in an ultrasonic instrument for ultrasonic treatment to disperse the materials evenly in the solution and avoid uneven molecular aggregation that may affect the experimental results.
[0084] ⑤ Use a fluorescence spectrometer to perform fluorescence spectral analysis on the DMSO solutions of the complex with different water contents. Use Origin to plot the measured fluorescence spectra on the same graph, and normalize some of the spectra to more intuitively observe the changes in fluorescence peak position and fluorescence intensity with different water contents.
[0085] ⑥Fix the position of the mobile phone and the UV lamp, and try to ensure that the focus, exposure and other performance of the mobile phone are completely consistent. Use a pipette to transfer 1800μL of a solution with a water content of 90% into a 10mm four-transparent quartz cuvette, and take photos and record. After taking photos, recycle the solution into the corresponding small glass bottle.
[0086] ⑦ Rinse the quartz cuvette with anhydrous ethanol first, then with dichloromethane. After washing, wipe off the unvolatile dichloromethane with a paper towel, and then wipe off the fine paper scraps on the quartz cuvette with high-grade lens paper.
[0087] ⑧Repeat steps ⑥⑦ to complete the photography of ten solutions with different water contents.
[0088] ⑨Use PS to combine ten photos into a group photo.
[0089] 2.2 Aggregation-induced emission performance results
[0090] Depend on Figure 7 As can be seen in Figure a, the maximum emission peak of OSA-TFBN in DMSO is at 440nm, showing blue light emission. As the water concentration increases, the blue light intensity gradually increases and then weakens. In order to prove the source of blue light emission, we tested the fluorescence spectrum of the single-component material in DMSO. Figure 7 As shown in Figure b, the blue light emission of the complex is basically consistent with TFBN, indicating that the blue light may come from TFBN. When the water concentration reaches 70%, yellow light begins to appear, and when the water concentration reaches 90%, the yellow light emission is the strongest, showing obvious aggregation-induced emission characteristics.
[0091] Depend on Figure 8 As can be seen in Figure a, the maximum emission peak of OOA-TEBN in DMSO is at 440nm, showing blue light emission. As the water concentration increases, the blue light intensity gradually increases and then weakens. In order to prove the source of blue light emission, we tested the fluorescence spectrum of the single-component material in DMSO, as shown in Figure 8 As shown in Figure b, the blue light emission of the complex is basically consistent with TFBN, indicating that the blue light may come from TFBN. When the water concentration reaches 80%, blue-green light appears. When the water concentration reaches 90%, the blue-green light emission is the strongest, showing aggregation-induced emission characteristics.
[0092] 3. Reversible optical properties under external temperature stimulation
[0093] 3.1 Sample preparation
[0094] ① Turn on the heating stage and set the temperature required for the test.
[0095] ② Prepare a clean glass sheet, two brackets, a UV lamp, and a clean medicine spoon. Calculate the grams of host and guest materials required based on a 1:1 molar ratio.
[0096] ③ Turn on the electronic balance, fold the weighing paper diagonally and place it on the balance, press the tare / zero key on the balance, and when the balance reads zero, use a medicine spoon to transfer an appropriate amount of medicine to the weighing paper. According to the known data, weigh 0.0100g of TFBN and 0.0100g of OSA for each experimental temperature, and weigh 0.0100g of TFBN and 0.0092g of OOA for the other material. After the balance reading stabilizes, record the number of grams weighed.
[0097] ④ Use a medicine spoon to transfer the weighed medicine to the glass slide so that the two single-component medicines are in contact with each other.
[0098] ⑤ Place a bracket on the left side of the heating table that has reached the set temperature to fix the mobile phone for recording video. Another bracket on the right side of the heating table is used to fix the UV lamp. Turn on the UV lamp and irradiate it on the heating table. Turn on the video mode of the mobile phone, adjust the magnification and focus, carefully transfer the glass piece to the heating table, and observe the reaction time of the two-component material.
[0099] ⑥After heating, turn off the heating table, transfer the heated material from the glass slide to the mortar, grind it thoroughly and collect it into the corresponding centrifuge tube.
[0100] ⑦ Clean used glass slides, medicine spoons, mortars and other instruments with anhydrous ethanol and dichloromethane, put them back in place, and put the medicines back into the medicine cabinet.
[0101] ⑧Turn off the electronic balance.
[0102] ⑨Process the recorded video, use PS to draw a group of screenshots processed at a certain time, and mark the corresponding time.
[0103] 3.2 Reversible optical properties under external temperature stimulation
[0104] First, the assembly ability of the donor and the acceptor at room temperature was studied. It was found that the assembly ability of the donor and the acceptor at room temperature was relatively weak, and the interface between OSA and TFBN hardly changed within 72 hours. Fig. 9 Then the assembly ability of OSA and TFBN at different temperatures (30℃, 35℃, 40℃, 45℃) was studied, and it was found that the OSA-TFBN complex was very sensitive to temperature and had a fast response speed. Fig.10It can be seen that when the temperature rises from 30℃ to 45℃, the response speed of OSA and TFBN is shortened from 45min to 75s, proving that with the increase of temperature, the response speed of OSA and TFBN assembly gradually increases. In addition, during the experiment, we found that at 45℃, the yellow fluorescence generated by the reaction will gradually quench as the heating time increases. Therefore, we studied the luminescence changes of the composite material at 45℃, such as Fig.11 As shown. The results show that when OSA-TFBN is at 45℃, the yellow fluorescence gradually quenches with the change of time. The experimental results show that 45℃ can quench the luminescence of the complex. The quenched complex is removed from the heating stage and placed at room temperature. When the temperature of the complex gradually cools down, it is found that the originally quenched complex gradually returns to its original yellow fluorescence with the increase of time, as shown in Fig.12 As shown. In summary, the OSA-TFBN complex is a temperature-sensitive material with reversible stimulus-responsive optical properties. The response speed of the complex is affected by temperature. The higher the temperature, the faster the response speed, and the lower the temperature, the slower the response speed. When a certain temperature is reached, the luminescent color of the complex is quenched. When the quenched complex is placed at room temperature and cooled, the quenched complex gradually recovers its original optical properties.
[0105] For OOA and TFBN, as in the former, we first studied the assembly ability of the donor and the acceptor at room temperature. We found that the assembly ability of the donor and the acceptor at room temperature was relatively weak, and the interface between OOA and TFBN hardly changed after 72 h. Fig.13 Then the assembly ability of OOA and TFBN at different temperatures (70℃, 80℃, 90℃) was studied, and it was found that OOA-TFBN was also sensitive to temperature and had a faster response speed. Fig.14 It can be seen that when the temperature rises from 70℃ to 90℃, the response speed of OOA and TFBN is shortened from 120s to 10s, proving that with the increase of temperature, the response speed of OOA and TFBN assembly gradually increases. In addition, during the experiment, we found that at 75℃, the blue-green light will gradually quench. Therefore, we studied the luminescence changes of the composite material at 75℃, such as Fig.15 As shown. The results show that when OOA-TFBN is at 75℃, the blue-green light gradually quenches over time. The experimental results show that 75℃ can quench the luminescence of the complex. When the quenched complex is placed at room temperature, as the temperature of the complex gradually cools, the originally quenched complex gradually returns to its original fluorescence color, as shown in Figure 1. Fig.16As shown. In summary, the OOA-TFBN complex is a temperature-sensitive, reversible stimulus-responsive material. The response speed of the complex is affected by temperature. The higher the temperature, the faster the response speed, and the lower the temperature, the slower the response speed. When a certain temperature is reached, the luminescent color of the complex is quenched. When the quenched complex is placed at room temperature and cooled, the quenched complex gradually recovers its original optical properties.
[0106] Depend on Fig.17 It can be seen that from the perspective of the heating temperature gradient change, the contact surface between SSA and TFBN has not changed at all. Combining the spectrum and the heating temperature gradient change diagram, SSA and TFBN did not form a eutectic, but only a simple physical doping process.
[0107] 4. Application of smart responsive organic luminescent materials in anti-counterfeiting
[0108] 4.1 Sample preparation
[0109] ① Prepare 3mL of 7×10 -2 mol / L OSA-TFBN complex in dichloromethane solution, set aside for later use. Prepare several filter papers with 2×2 cm patterns, cut or make corresponding patterns according to experimental needs, wet the filter paper with the complex in dichloromethane solution, and wait for the filter paper to dry at room temperature.
[0110] ② Under the irradiation of ultraviolet light, give the filter paper a certain temperature, observe the changes in the luminous color of the filter paper where the ultraviolet light irradiates, and take photos to record.
[0111] ③Wait for a while, observe the changes in the luminous color of the area irradiated by the ultraviolet light, and repeat steps ② and ③.
[0112] 4.2 Anti-counterfeiting application results
[0113] Based on the reversible optical properties of the composite material under external temperature stimulation, the present invention selects the dichloromethane solution of the OSA-TFBN composite to design a reversible temperature anti-counterfeiting application. When the filter paper is soaked with the dichloromethane solution of OSA-TFBN, it is observed under ultraviolet light that the originally soaked filter paper gradually emits yellow fluorescence as the solvent evaporates. Fig.18 Schematic diagram of the reversible luminescence process of OSA-TFBN under ultraviolet light. When the ultraviolet light is irradiated at a close distance to the pattern below, the luminescence color of the area irradiated by the ultraviolet light is quenched. As time goes by, the originally quenched area gradually recovers to yellow luminescence. Fig.19 This is a schematic diagram of the four rounds of reversible fluorescence changes of OSA-TFBN. Color quenching occurs where ultraviolet light is irradiated, that is, the composite material is sensitive to temperature, and the color quenches where the temperature rises. When the heat source is removed, the luminescent color recovers after a certain period of time. Fig. 20The composite material was shown to have good repeatability, and after four rounds of writing and erasing, the material still maintained good optical properties.
[0114] 5. Conclusion
[0115] The present invention prepares a series of smart responsive organic donor-acceptor composite materials based on 3,4,5,6-tetrafluorophthalonitrile (TFBN) as an acceptor material, and phenoxathiophene (OSA) and dibenzodioxin (OOA) as donor materials. These composite materials not only exhibit unique optical properties, but also show significant optical responses under external stimuli, providing broad possibilities for future applications.
[0116] The present invention observed that when the donor material is phenoxathiophene (OSA), the prepared composite exhibits yellow light emission when subjected to external stimulation. When the donor material is replaced with dibenzodioxin (OOA), the composite exhibits blue light emission, providing diversity for the application of composite materials in the optical field.
[0117] In order to prove the successful design and synthesis of the composite material, the present invention uses a fluorescence spectrometer to conduct an in-depth analysis of it. By comparing the spectral characteristics of the single-component material and the composite material, we found that the spectrum of the composite material showed a more obvious red shift compared with the spectrum of the single-component material. This change proves that a new substance has been produced. In addition, the structure of the composite material was characterized by an X-ray diffractometer. The results show that the composite material has diffraction peaks different from those of the single-component material. These spectra further prove that the composite material is not a simple physical doping of two single-component materials under external force stimulation, but has formed a relatively stable structure.
[0118] In further research, the present invention found that both composite materials exhibit unique aggregation-induced emission properties. When the composite materials are aggregated together, their luminescence performance will be enhanced. This property makes these materials have potential application value in fields such as bioimaging. What is more worth mentioning is that these materials are highly sensitive to temperature and exhibit reversible stimulus response characteristics. The experimental data clearly show that as the temperature increases, the response speed of the material increases significantly; and when the temperature decreases, the response speed slows down accordingly. When the temperature reaches a certain value, the luminescence color of the composite material will be quenched. However, when these quenched composites are placed at room temperature and cooled, they can gradually restore their original optical properties. This shows that the composite material has reversible optical properties under external temperature stimulation. This reversible optical property makes these materials have great application potential in the fields of information storage, anti-counterfeiting encryption, and sensing.
[0119] In summary, the smart responsive organic donor-acceptor composite material prepared by the 3,4,5,6-tetrafluorophthalonitrile (TFBN) acceptor material and the phenoxathiol (OSA) and dibenzodioxin (OOA) donor materials of the present invention not only exhibits unique optical properties and aggregation-induced luminescence properties, but also has reversible stimulus response properties. These excellent properties make these materials have broad application prospects in the fields of sensing, information storage, anti-counterfeiting encryption, etc.
[0120] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing an intelligent responsive organic light-emitting material, characterized in that: The following steps are involved: With 3,4,5,6-tetrafluorophthalonitrile as an acceptor and thiophene or dibenzodioxin as a donor, the acceptor and the donor are self-assembled by a grinding method to obtain an intelligent response type organic light-emitting material.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the 3,4,5,6-tetrafluorophthalonitrile to thiophene or dibenzodioxin is 1:
1.
3. The preparation method according to claim 1, characterized in that: 3,4,5,6-tetrafluorophthalonitrile and phenoxathiophene or dibenzodioxin are mixed and ground to obtain a smart response type organic light-emitting material.
4. The preparation method according to claim 3, characterized in that: The grinding time is 1 to 4 minutes.
5. An intelligent responsive organic light-emitting material prepared by the preparation method according to any one of claims 1 to 4.
6. The smart response type organic light emitting material according to claim 5, characterized in that: The aggregation-induced luminescence of the smart responsive organic light-emitting material is yellow light or blue-green light.
7. Use of the smart responsive organic light-emitting material according to claim 6 in preparing temperature responsive anti-counterfeiting materials.
8. The use according to claim 7, characterized in that: The application is specifically as follows: preparing a dichloromethane solution of the smart responsive organic light-emitting material, and using the solution to soak the anti-counterfeiting material, and then drying at room temperature.
9. The use according to claim 8, characterized in that: The concentration of the dichloromethane solution of the smart response type organic light-emitting material is 0.05 mol / L to 0.07 mol / L.
Citation Information
Patent Citations
Fluorescent probe compound with luminescence property in solid state after grinding and preparation method thereof
CN110283193A
Blue light-emitting compound for organic electroluminescent apparatus and organic electroluminescent apparatus utilizing the same blue light-emitting compound
CN1468933A
Compound, light-emitting material and light-emitting device
JP2023097788A